Skew-symmetric matrices and integral curves in Lorentzian spaces - Tunahan Turhan; Nihat Ayyıldız (Kuwait Journal of Science)
We provide some existence results about integral curves of a linear vector field on 3-dimensional Lorentzian space E₁³. Moreover, we have a classification of integral curves ( or flow lines ) of a linear vector field and the normal forms of the matrix corresponding to a mapping A in Lorentzian spaces E₁³ and E₁²ⁿ⁺¹.